2003
DOI: 10.3346/jkms.2003.18.4.534
|View full text |Cite
|
Sign up to set email alerts
|

Intake of Dietary Fat and Vitamin in Relation to Breast Cancer Risk in Korean Women: A Case-Control Study

Abstract: To investigate association between breast cancer risk and nutrients intake in Korean women, a case-control study was carried out, at Seoul, Korea. Incident cases (n=224) were identified through the cancer biopsy between February 1999 and December 2000 at two University hospitals in Seoul. Hospital-based controls (n=250) were selected from patients in the same hospitals, during the same periods. Food intake was investigated semiquantitative frequency questionnaire (98 items) by trained dietitian. Subjects were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 26 publications
1
22
0
1
Order By: Relevance
“…Secondly, different controls of the study population, the heterogeneity decreased in both subgroups of controls (except b-carotene, the heterogeneity only decreased in population-based case-control studies) in subgroup analyses based on types of control. Finally, different stages of breast cancer patients, 2 of the 24 case-control studies selected invasive breast cancer patients [17,24], one of the 24 case-control studies selected early-stage breast cancer patients [26]. Whereas other studies selected all the in situ, early-stage, and invasive breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, different controls of the study population, the heterogeneity decreased in both subgroups of controls (except b-carotene, the heterogeneity only decreased in population-based case-control studies) in subgroup analyses based on types of control. Finally, different stages of breast cancer patients, 2 of the 24 case-control studies selected invasive breast cancer patients [17,24], one of the 24 case-control studies selected early-stage breast cancer patients [26]. Whereas other studies selected all the in situ, early-stage, and invasive breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…No meta-analysis about the associations between a-carotene, b-cryptoxanthin, lutein/?zeaxanthin, and lycopene and breast cancer has been reported. Since the first two metaanalyses were published, 20 inconsistent observational studies with large samples have been published [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Meanwhile, among the carotenoids, which one play a greater role in reducing breast cancer risk remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The high heterogeneity in this metaanalysis may be due to the following reasons: (1) various ages of the study population; (2) the different stages of breast cancer patients, 5 case-control studies only involving invasive breast cancer patients [16,17,25,29,32]; (3) the bias from the collection of dietary information, the definition of food groups, and the diverse time periods before interview across studies especially in the case-control studies.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Vitamin C intake, has also had conflicting reports of both null and nonsignificant inverse associations with breast cancer risk [18,[39][40][41]44,48]. However, several case-control studies [16,49,50] and one meta-analysis [20] reported a significant inverse association for vitamin C intake. In our study, we found breast cancer risk associated with use of a B-vitamin supplement varied according to dietary intake.…”
Section: Discussionmentioning
confidence: 99%